151k views
1 vote
F(x)=8x^2-2x+3

g(x)=12x^2+4x-3

What is h(x)=f(x)-g(x)?

A) h(x)=20x^2+2x
B) h(x)=-4x^2-6x
C) h(x)=-4x^2-6x+6
D) h(x)=-4x^2+2x

2 Answers

6 votes

Answer:

-4x^2-6x+6

Explanation:

We are asked to subtract g from f.

So the problem is:

[8x^2-2x+3]-[12x^2+4x-3]

So I'm going to distribute and write without [].

8x^2-2x+3-12x^2-4x+3

Now I'm going to pair up any like terms:

8x^2-12x^2-2x-4x+3+3

Simplifying:

-4x^2-6x+6

User Edwin Buck
by
6.0k points
0 votes

Answer: The correct option is

(C)
h(x)=-4x^2-6x+6.

Step-by-step explanation: We are given the following two functions :


f(x)=8x^2-2x+3,~~~~~g(x)=12x^2+4x-3.

We are to find the value of h(x) if h(x) = f(x) - g(x).

To find the value of h(x), we must subtract the expression of g(x) from the expression of f(x).

The value of h(x) can be calculated as follows :


h(x)\\\\=f(x)-g(x)\\\\=(8x^2-2x+3)-(12x^2+4x-3)\\\\=8x^2-2x+3-12x^2-4x+3\\\\=-4x^2-6x+6.

Thus, the required value of h(x) is
-4x^2-6x+6.

Option (C) is CORRECT.

User Rashae
by
6.1k points